PERTANGGUNGJAWABAN PERSEROAN TERBATAS TERHADAP SURAT KETETAPAN PAJAK (LIMITED COMPANY LIABILITY TO THE TAX ASSESSMENT LETTER) - Ananda, Denny Mulia (Universitas Harapan Medan, 2023)
A tax assessment letter is a record of a company's financial information in an accounting period that can be used to describe the company's performance. Fiskus in carrying out their authority in issuing an STP, SKPKB, SKPKBT must be based on the attribution of authority given by laws and regulations but in current implementation there are problems where there are differences between accountability under the Limited Liability Company Law and the Tax Collection Law. This research uses a type of normative legal research that is descriptive- analytic in nature, using secondary data, namely primary legal materials. The results of this study include the efforts of the tax authorities to deal with STP, SKPKB, SKPKBT which are not paid by Limited Liability Companies is to enforce the law through tax collection which is enforceable under the Law of the Republic of Indonesia Number 19 of 2000 concerning Amendments to Law Number 19 of 1997 concerning Tax Collection By Forced Letter (Tax Collection Law With Forced Letter). The billing action begins with the issuance of a letter of reprimand, a warrant, execution of confiscation and then conducts an auction. Underpaid and unpaid SPT, SKPKB, SKPKBT organs of a limited liability company where according to Article 14 paragraph (1a) of the Law on Collection of Taxes by Enforcement Letter, if the assets of a limited liability company cannot pay off the said tax assessment letter, then the organs of a limited liability company may be subject to confiscation of the assets. personally not only directors or commissioners but .also shareholders. Tax collection regulations are special rules relating to tax debts which are different from debts in general and can also be understood as tax collection regulations which are laws that have a goal for the benefit of society at large so that they can override personal interests.